The Development of Student’s Book Based on STEM (Science Technology Engineering and Mathematics) with LBL (Life Based Learning) Integration on The Subject of Biotechnology in Class XII Senior High School - Fatmawati Ningsih; Suratno Suratno; Erlia Narulita (Pancaran Pendidikan, 2018)
The development of science and technology in the 21st century is increasingly leading to make biotechnology as one of the disciplines that must be mastered by learners. Learners need a good understanding of biotechnology so that the knowledge they have gained can be applied in everyday life and provide the life skills to the students. One of his efforts is the use of student’s book based on the STEM with LBL integration. This research is a development research using ADDIE model consisting of five stages namely analysis, design, development, implementation and evaluation. The value of the validity of the student ‘s book is 92% with a category very valid. The practical value of the student’s book based on student questionnaire is 88,8% and the observation value of learning implementation is 89,5% so that student's book can be used in the learning subject of biotechnology class XII high school in Jember.